Economic Impacts of Cultural Diversity in the Netherlands: Productivity, Utility, and Sorting - Jessie Bakens; Peter Mulder; Peter Nijkamp (Tinbergen Institute, 2012)
This paper identifies the role of cultural diversity in explaining spatial disparities in wages and housing prices across Dutch cities, using unique individual panel data of home owners. We distinguish between the effects of interactions-based productivity, consumption amenities and sorting of heterogeneous home owners while controlling for interactions between the labor and housing market. We find that an increase in the cultural diversity of the population positively impacts equilibrium wages and housing prices, particularly in the largest and most densely populated cities. This result is largely driven by spatial sorting of individuals in both the labor and housing market. After controlling for home owner heterogeneity we find that increasing cultural diversity no longer impacts local labor markets and negatively impacts local housing markets. The latter result is likely to be driven by a negative causal effect of increased cultural diversity on neighb orhood quality that outweighs a positive effect of increased cultural diversity in consumption goods.
urn:NBN:nl:ui:31-1871/38475
Keywords: J31; R21; R23; R31; 330; cultural diversity; immigrants; local amenities; sorting; housing prices; productivity; Kulturelle Identität; Migranten; Arbeitsproduktivität; Immobilienpreis; Haushaltseinkommen; Niederlande